Specific Characteristics of Forming the Pedagogical Competence of the Teacher of Physical Education in the Higher Education System - Gilijova Arzigul Mametmiratovna (Zien Journals, 2022)
In this article,development of physical education and sports, pedagogical concept of competence, special social skills,Pedagogical component, to determine the theoretical basis of the formation of the pedagogical competence of the future physical education teachersuch issues are disclosed.
Keywords: Physical education; pedagogical competence; cognitive; discipline